Pemodelan Shift Kerja dalam Proyek Konstruksi menggunakan NetLogo dalam meminimalkan Penyebaran Covid-19 - Sandi Wahyudiono; Azhar Adi Darmawan; M Shochibul Burhan (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Due to a shift in habits from face-to-face to virtual activities, the Covid-19 pandemic in Indonesia has affected the way people interact with each other and the environment. However, other activities, such as in the construction industry, are not digital. In Indonesia, the outbreak has had a significant impact on construction projects. Due to the pandemic, construction projects may involve local workers mixed with migrant workers, which could potentially result in new clusters of Covid-19 spread. This study presents an Agent Based Modeling (ABM) by using NetLogo approach to assess the impact of using multiple shifts to reduce the spread of Covid-19. ABM is a simulation model that describes individuals (agents) in a complex and dynamic system. This model is based on literature data to replicate worker behavior across shifts and simulate scenarios using various alternatives during a pandemic. Therefore, estimates and scenarios are needed to realize the Covid-19 simulation among construction projects. From the results of modeling using Netlogo, it can be seen that when shifts are divided into several scenarios, the number of hecalthy workers can increase compared to only one shift. The best scenario is to distribute 30% of project workers into night shift. By implementing various alternative work shifts, it is expected that they can contribute to minimizing the spread of Covid-19 among construction workers which can be implemented by the Project Manager.